Development of biomechanically optimized sledges for nordic disabled skiers for Sochi 2014 - Scherge, M.; Rombach, R.; Gollhofer, A.; Rapp, W. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
For the Winter Paralympics 2014 in Sochi research was going on to create optimized sledges for impaired cross-country and biathlon athletes based on biomechanical relationships. The challenge in relation to this is that the degree and nature of the impairment is different for each athlete and that athletes can only optimally utilize their strength for forward propulsion in a very specific seated position. For this reason, each athlete essentially requires an individual solution in construction of sit sledges.